Rapport från varumärkenas produktionsfält - Galli, Raoul (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
From the viewpoint of an international advertising agency in Stockholm, this article sketches some important power lines that structure the social space within which "creators" and "curators" in the Swedish advertising industry perform their actions. Inspired by Pierre Bourdieu's field theory, Galli also examines the tense relation between a field of production specialized in constructing specific symbolic products known as brands, and a world of legitimate cultural production. In the field of brand production different sorts of recognized skills and resources render its possessors communicative capital, an active property expressed in objectified, institutionalized, and embodied states like awards, membership in field-specific boards and juries, and the bodily capacity to master social presentations. A study of "brand-day workshops" rounds off the text suggesting that institutional and individual agents in the field of power not only aim at perpetuating and controlling brand competition through advertising and branding, but also the more hidden dimension of already existing social distinctions and divisions.